THE INFLUENCE OF SOCIAL CAPITAL AND RATIONALITY ON MSME PERFORMANCE THROUGH INNOVATIVE WORK BEHAVIOR AND ENTREPRENEUR LEARNING ORIENTATION IN JAMBI CITY - Muazza, Muazza; Mayasari, Mayasari; Amin, Shofia; Razak, Mohamad Idham Haji Md (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
This study analyzes the impact of Social Capital and Rationality on the performance of MSMEs in Jambi City, mediated by Innovative Work Behavior and Entrepreneur Learning Orientation. Using a quantitative approach with PLS-SEM, data were collected from MSME actors to examine these relationships. The findings reveal that Social Capital has a positive but insignificant influence on MSME performance, indicating that social networks may not directly enhance outcomes due to limited resource access or ineffective linkages. In contrast, Rationality shows a significant negative effect on performance, suggesting that highly rational decision-making can reduce adaptability in dynamic markets. Interestingly, both Social Capital and Rationality significantly improve Innovative Work Behavior, but this behavior negatively impacts performance possibly due to innovation not aligning with market needs or requiring time to show results. Meanwhile, Entrepreneur Learning Orientation has a significant positive influence on performance, emphasizing the role of continuous learning. Rationality supports learning orientation, while Social Capital does not. Overall, these findings highlight the complex dynamics shaping MSME success and offer strategic insights for development in Jambi City.